ZnO as an effective hole transport layer for water resistant organic solar cells - Chi, Cheng-Yu; Sauter, Eric; Zharnikov, Michael (Journal of materials chemistry. A, Materials for energy and sustainability, 2018)
Organic solar cells (OSCs) are a major contender for third generation photovoltaic systems. However, the scalability and potential commercial viability of OSCs are still limited due to their instability under hostile ambient conditions such as a humid atmosphere. One of the major limiting factors in this context is the water-solubility of the hole transport layer (HTL). As a solution to this problem, in the given work, we report the design of an ultrathin, water-resistant and p-type-like conducting ZnO film serving as a HTL for inverted OSCs. This film is fabricated using ultrasonic spray pyrolysis under ambient conditions and subsequently transferred onto the active layer of the OSC using a sacrificial poly(styrenesulfonate) (PPS) film. The resulting ZnO film has oxygen-rich and zinc-deficient characteristics which stem presumably from a gradient-like doping of PSS chelating with zinc species. These characteristics result in a suitable energy level realignment and facilitate p-type-like charge transport to the anode. The fabricated device has excellent stability and only minor loss in performance upon a prolonged immersion in water without encapsulation, in striking contrast to the commonly used MoOx HTL OSC which was completely deteriorated.
Gesehen am 25.04.2019